P Pembuatan dan Pemasangan Papan Penanda Batas Wilayah Pada Kegiatan KKN Di Desa Tambak Sirang Baru : Design and Installation of Village Boundary Signage through Community Service Program in Tambak Sirang Baru Village - Jainudin, Jainudin; Ansari , Hafiz; Faiyin, Dwi Irfan; Jumiati, Jumiati; Anggraini, Septia; Nur, Muhammad Ikhsan; Masruroh, Silfiana Ila; Syaikhani, Ahmad (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
Tambak Sirang Baru Village is an area with vast agricultural potential and an active social environment. However, the village faces challenges related to spatial identity due to the absence of boundary signage for administrative areas and neighborhood units (RT). This lack of informational infrastructure makes it difficult for residents and visitors to recognize administrative boundaries and hinders the effectiveness of area-based public services. Through the Community Service Program (KKN), university students collaborated with the local community to design and install boundary signage. The program was conducted over one month using a participatory approach consisting of five stages: initial observation, program planning, signage production, installation, and evaluation. KKN students worked closely with village officials and residents at every stage, from site surveys and signage design to material procurement, installation, and impact evaluation. A total of 12 signs were successfully installed at strategic village locations. The main material used was ulin wood, painted in green, blue, and black. Evaluation results showed that the signage functioned effectively, was easy to read, and strengthened the village’s spatial identity. Village officials and residents responded positively to the presence of the signage, noting its contribution to aesthetics and improved spatial orientation.